The appearance of pulmonary alveolar microlithiasis on dual-energy X-ray absorptiometry - Fathala, Ahmed; Alduraibi, Alaa (The European Research Journal, 2018)
Dual-energy X-ray absorptiometry (DEXA) scan has been widely used as standard method of assessing bone density. Artefacts and incidental findings are frequently encountered on the DEXA scan images, some of which may affect bone mineral density values and the others are only of incidental findings. In this case report, we present a 44-year-old male diagnosed with pulmonary microlithiasis that was confirmed on a transbronchial biopsy. To our knowledge, we report the first case in the literature, describing the appearance of pulmonary alveolar microlithiasis on DEXA scan with brief review of literature on both pulmonary alveolar microlithiasis and artifacts and incidental findings encountered on DEXA scan.